Bedrock river incision response to basin connection along the Jinshan Gorge, Yellow River, North China. (15th December 2015) - Liang, Hao; Zhang, Ke; Fu, Jianli; Li, Li; Chen, Jun; Li, Shubo; Chen, Liye
Highlights: Longitudinal profile shows diachroneity along terraces and acceleration on incision. The connection of the basins accounts for the rapid incision of the Jinshan Gorge. Two down-cutting events solve debate on the forming age of the Jinshan Yellow River. Abstract: The Jinshan Gorge of the Yellow River, connecting the Hetao and the Fenwei Basins, is a key area for understanding the formation and evolution of the drainage system in response to bedrock river incision. We have measured fluvial terraces along the gorge in the field in detail. The longitudinal profile and published dating of terraces indicate that rapid river incision occurred in the late Pleistocene. The deactivated boundary faults and uniform lithology of the gorge have no measurable influence the incision. Changes in precipitation are consistent with incision rate in late Pleistocene, rapid in MIS5 and low in MIS3, whereas appearing inconsistent in MIS7 when high rainfall was associated with low incision rates. We infer the variation of discharge to large paleolakes drainage in response to connection of the Hetao and Fenwei Basins. Revealed by lacustrine platform in these two basins, fast paleolake regressions took place approximately at 0.22 Ma in the Fenwei Basins, leading to base level fall, and then 0.10 Ma in the Hetao Basins, causing an abrupt increase in discharge. These two events made major contributions to the rapid bedrock river incision.